ACADEMIC BURNOUT AND EXAM ANXIETY AS PREDICTORS OF EXAM MALPRACTICE AMONG UNDERGRADUATES IN ENUGU STATE - Ozochi, Alexander C. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Examination malpractice has been a significant challenge in Nigeria's educational system. The trend is pervasive across all levels of schooling and has downgraded the integrity of the assessment processes. Past research has underscored the pattern and prospects of exam malpractice. However, little is known about the influence of burnout and exam-related uneasiness. The present study examined academic burnout and exam anxiety as predictors of exam malpractice in undergraduates in Enugu state. Two hundred and thirty-three undergraduates enrolled in public tertiary institutions in Enugu State, Nigeria, participated in the study. The respondents completed a self-report measure of the cognitive test anxiety scale, academic burnout scale, and exam malpractice questionnaire. A cross-sectional design was employed in the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, Version 23). Multiple regression was computed to test the main hypotheses of the study. The result indicated that academic burnout and exam anxiety significantly predicted exam malpractice, F (2, 231) = 31.25, p < 0.05. All two variables added statistically significantly to the prediction and contributed about 13.4% of the variance in exam malpractice. The result has implications for combating cheating in academia and provides crucial data for research.